Coordination of Strategies and Programs for EU and State-Funded Investments in Romania’s Infrastructure - World Bank Group (World Bank, Washington, DC, 2016)
This report provides a diagnostic and a set of recommendations for the coordination of infrastructure investments in three main sectors in Romania: roads; water and wastewater; and social infrastructure (education, health, culture, and sports). The proposals formulated are targeted primarily at the main client of this work, the Ministry of Regional Development and Public Administration (MRDPA) and specifically at the Directorate General for Regional Development and Infrastructure (DG RDI), which manages the most important state-budget-funded program for local infrastructure investments – the National Local Development Program (PNDL). Other key stakeholders include the Center of Government (CoG), the Ministry of Public Finances, the Ministry of European Funds, other central authorities in charge of EU and/or state-funded investment programs, Regional Development Agencies, and county and local councils. While customized for the PNDL, the recommendations that follow can be replicated across all state-budget-funded investment programs. This report presents multiple instruments for promoting coordination: dedicated platforms, harmonization of investment programs (design, financing criteria, producers), and knowledge sharing of good practices at the local level.